Cutaneous Radiation-Associated Angiosarcoma After Cervical Cancer Treatment: A Case Report - Cong-Cong Xu; Wei Zhang; Hao Chen (Wolters Kluwer Health, 2021)
Abstract. Introduction:. Cutaneous radiation-associated (cRAA) angiosarcoma is a rare malignant neoplasm derived from vascular endothelial cells, but a relatively commonly recognized complication of radiation therapy. Here, we present a patient with cRAA, who undergone radiochemotherapy for cervical cancer 11 years ago. Case presentation:. A 48-year-old woman presented with a 6-month history of painless purple skin plaques and nodules on her lower abdomen and right thigh. The patient had undergone radiochemotherapy for cervical cancer 11 years ago. A skin biopsy showed a diffuse proliferation of irregular anastomosing dilated vascular structures with atypical endothelial cells. She was diagnosed as cRAA according to clinical and histological manifestations. Discussion:. cRAA is a rare malignant neoplasm but it is a complication of radiation therapy. The incidence of cRAA has increased in recent years. Clinical and pathological manifestations are highly varied. Radical resection is the preferred treatment. Conclusion:. Patients with suspicious violaceous lesions should undergo biopsy. Clinical suspicion and pathological examination are of the utmost importance for cRAA.